2018
DOI: 10.1007/s13105-018-0637-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical training improves thermogenesis and insulin pathway, and induces remodeling in white and brown adipose tissues

Abstract: Physical training (PT) has been considered as a treatment in metabolic syndrome (MS), since it induces thermogenic activity in brown (BAT) and white (WAT) adipose tissues. We evaluated the therapeutic effect of PT on activity of WAT and BAT in rats with MS induced by high-fat diet (30% lard) for 13 weeks and submitted, for the last 6 weeks, to swimming or kept sedentary (SED) rats. MS-SED rats compared to control diet (CT-SED) rats showed low physical fitness and high levels of glucose, insulin, homeostasis ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Adiposity index was measured by the formula [inguinal fat + epididymal fat + retroperitoneal fat absolute] [15].…”
Section: Methodsmentioning
confidence: 99%
“…Adiposity index was measured by the formula [inguinal fat + epididymal fat + retroperitoneal fat absolute] [15].…”
Section: Methodsmentioning
confidence: 99%
“…Exercise is an effective therapy to improve glucose metabolism and insulin sensitivity in skeletal muscle [80,81], heart [82], and WAT [28,83]. Since BAT plays an important role in regulating glucose metabolism, several studies have investigated how exercise can affect glucose uptake in BAT [29,33,72,73,79] (Table 1).…”
Section: The Role Of Bat In Glucose Metabolism In Response To Coldmentioning
confidence: 99%
“…Some rodent studies have shown that exercise (treadmill training or swimming) [29,72] increases the expression of proteins related to insulin signaling in BAT. This would indicate an increase in glucose uptake into BAT, but that was not directly measured in these studies.…”
Section: The Role Of Bat In Glucose Metabolism In Response To Coldmentioning
confidence: 99%
“…Although AMPK was not measured in the current study, it may explain the increase in GLUT4 in response to training, independent to the insulin signalling cascade. In rodent models, exercise training has been shown to increase the enzymes associated with mitochondrial biogenesis, oxygen consumption rate, GLUT4 and reduce UCP2 in SAT (inguinal) 29,30 . Similarly, aSAT was the only depot in which oxygen flux through Leak ETF respiration was reduced and mitochondrial coupling control ratios increased, which was further supported our increase in GLUT4 gene expression in response to exercise training.…”
mentioning
confidence: 99%